PENGAWASAN SUMBER DAYA KELAUTAN DAN PERIKANAN DALAM PEMBERANTASAN KEGIATAN ILLEGAL FISHING OLEH NELAYAN ASING DI KABUPATEN KEPULAUAN ANAMBAS PROVINSI KEPULAUAN RIAU TAHUN 2013-2015 - Putri, Rizki Zukmadianty; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The background of this research is a case of illegal fishing in the waters of Anambas increasing by 2013-2015 and were carried out by foreign fishermen. This research seeks to know the form of surveillance in the eradication of illegal fishing activities by foreign fishermen in the Anambas Islands Regency and also find out what factors hampered in the exercise of supervision of marine resources and fisheries and also the eradication of illegal fishing activities in the waters of Anambas.This research was conducted in the Anambas Islands Regency namely Department of marine and Fisheries and the Anambas Islands Regency Office Satker Tarempa PSDKP. The research method used was qualitative approach that will produce the descriptive data aims to describe the real state of affairs in the field in a systematic and accurate facts or analysis related research, as well as observations based on the particular information or data. The technique of data collection is done with the interview, observation and documentation.The results of this study explains that there are three forms of surveillance in the eradication of illegal fishing in Anambas Island Regency. Three forms of surveillance are legislative surveillance by DPRD of Anambas Island Regency, judicial surveillance by the ad hoc judisial for fishery law enforcement, and administrative and supervision by a team of joint operational surveillance of fisheries resources in surveillance at sea of a foreign ship and permissions related standard catching fish. Restricting factors of supervision and the eradication of illegal fishing is the lack of communication and coordination between team members combined supervision, absence of home detensi immigration, the budget for the supervision of the supervisor, the ship is still inadequate, and also human resources (HR).Keywords: supervision, Marine Resources and fisheries, Illegal Fishing.